Risk reporting: Do country-level institutional forces really matter? - Serrasqueiro, R. M.; Oliveira, J. (Asian Review of Accounting, 2022)
The annual reports of the non-financial European firms listed at the Euro Stoxx-50 index over the period of 2007 and 2011 were content analysed. This study intends to address two main issues: to what extent the country-level institutional forces compel (directly) firm’s risk reporting behaviour and in which way these country-level institutional forces moderate the relationship between risk reporting and firm-level characteristics. Main findings indicate that, during this period the European listed companies disclosed more risk information on a voluntary basis (such as operational and strategic risks) and with better informative content (more forward-looking and focused on positive news). Consistent with institutional theory, findings confirm that the country-level institutional forces explain variations on risk reporting. Additionally, it also indicates that the relationship between risk reporting and leveraged firms is weaker among countries with stronger institutional forces. These findings have several implications for investors and regulators in Europe basically in helping achieve efficiency in investment decisions and to stimulate further efforts to improve risk reporting regulations. This study makes two major contributions. First, it extends Elshandidy’s et al. (2015) work by using other country-level institutional forces that capture the efficacy of corporate boards, the protection of minority shareholders’ interests, country’s level of democracy, law enforcement mechanisms, and press freedom. Second, it uses firms that are considered as a Blue-chip representation of super-sector leaders in the Eurozone (but from different institutional contexts). This research setting can be more insightful in shedding some light towards our understanding on how these leading firms can promote innovative and high quality level of RR and how country-level driving forces influence these variables.